QRIS Impactfull: How to Develop Traditional Market Financial? - Nafis, Mochammad; Pujianto, Wahyu Eko; Qurratu’aini, Nafia Ilhama; Sholikhah, Afifatus (Dinasti Publisher, 2025)
Traditional markets face various environmental challenges that ultimately affect their performance practices; this study aims to analyse digital literature on digital transactions with local knowledge as moderation. Sampling technique: This research was conducted in traditional markets in the Sidoarjo district and involved 263 respondents, including shop owners. Data analysis using quantitative methods, such as SmartPLS 4.0 software, was used to test the research hypothesis. Digital literacy significantly influences the adoption of digital transactions in traditional markets, such as QRIS. Good digital literacy and skills increase the likelihood of merchants adopting the technology significantly when moderated by local knowledge that reinforces the application of technology according to local culture and economic practices. Financial education also encourages digital transactions; merchants who understand financial management are more likely to switch to digital payment systems. Local knowledge strengthens the influence of financial education by tailoring technology to market needs. This study highlights the importance of digital literacy, financial education and the local socio-cultural context in modernising traditional markets in Sidoarjo.